Flexible titanium nitride/germanium-tin photodetectors based on sub-bandgap absorption - An, Shu (2022)
We report an enhanced performance of flexible titanium nitride/germanium-tin (TiN/GeSn) photodetectors (PDs) with an extended photodetection range based on sub-bandgap absorption. Single-crystalline GeSn membranes transfer-printed on poly(ethylene terephthalate) are integrated with plasmonic TiN to form a TiN/GeSn heterojunction. Formation of the heterojunction creates a Schottky contact between the TiN and GeSn. A Schottky barrier height of 0.49 eV extends the photodetection wavelength to 2530 nm and further enhances the light absorption capability within the detection range. In addition, finite-difference time-domain simulation proves that the integration of TiN and GeSn could enhance average absorption from 0.13 to 0.33 in the near-infrared (NIR) region (e.g., 1400-2000 nm) and more than 70% of light is absorbed in TiN. The responsivity of the fabricated TiN/GeSn PDs is increased from 30 to 148.5 mA W-1 at 1550 nm. There is also an ∼180 nm extension in the optical absorption wavelength of the flexible TiN/GeSn PD. The enhanced performance of the device is attributed to the absorption and separation of plasmonic hot carriers via TiN and the TiN/GeSn junction, respectively. The effect of external uniaxial strain is also investigated. A tensile strain of 0.3% could further increase the responsivity from 148.5 to 218 mA W-1, while it is decreased to 102 mA W-1 by 0.25% compressive strain. In addition, the devices maintain stable performance after multiple and long bending cycles. Our results provide a robust and cost-effective method to extend the NIR photodetection capability of flexible group IV PDs.